2021
DOI: 10.3390/app112110455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Different Types of Mineral Trioxide Aggregate Cements as Direct Pulp Capping Agents in Human Teeth

Abstract: Traumatic human dental injuries involving the pulp might necessitate direct capping procedures. This clinical study aimed to analyse the histological outcomes using two different direct capping materials. Twenty patients with bilateral premolars, scheduled for orthodontic extraction, were selected. The teeth were treated either using ProRoot MTA or RetroMTA. All patients were recalled after 30 and 60 days for teeth extraction. The histopathologically stained specimens were blindly evaluated using hard tissue b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Ballal et al compared smear layer removal in the incisor teeth and found that EndoUltra was more effective in the apical area than the side-vented or EndoSafe irrigation system. 36 Karade et al achieved significantly better cleanliness with EndoUltra than with EndoActivator in the apical third areas of the premolar. 37 Sartiono and Iskandar also found EndoUltra effective in debris removal in the apical third area of mandibular premolars.…”
Section: Discussionmentioning
confidence: 98%
“…Ballal et al compared smear layer removal in the incisor teeth and found that EndoUltra was more effective in the apical area than the side-vented or EndoSafe irrigation system. 36 Karade et al achieved significantly better cleanliness with EndoUltra than with EndoActivator in the apical third areas of the premolar. 37 Sartiono and Iskandar also found EndoUltra effective in debris removal in the apical third area of mandibular premolars.…”
Section: Discussionmentioning
confidence: 98%
“…4 This dentin bridge formation aims to preserve the pulp in its vital condition after the injury. 4,[11][12][13] Dentinal bridges lead to the formation of a calcified barrier, which is advantageous in pulp-capping procedures for dentin formation. 12 The biomaterials used for direct pulp-capping treatments include calcium hydroxide, resin-modified glass ionomer cements (RMGICs), mineral trioxide aggregate (MTA) and calcium silicate-based cements (CSCs).…”
Section: Discussionmentioning
confidence: 99%
“…2,11 Biomaterial application in the injured areas after excavation aims to form dentinal bridges. 3,12 Calcium hydroxide and mineral trioxide aggregate (MTA) can be used in pulp-capping therapy, which is applied after the dental injury. 3,12,13 Calcium hydroxide, a gold standard material, was commonly used decades ago for direct pulpcapping therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Retro-MTA has a shorter setting time compared to the ProRoot MTA and has no discoloration potential, due to the presence of zirconium oxide as an alternative radiopacifier to bismuth oxide [ 6 ]. Ballal et al reported that Retro-MTA healed pulp tissue faster than ProRoot MTA when used as a direct pulp capping agent [ 7 ]. Ortho-MTA has a similar composition to ProRoot MTA.…”
Section: Introductionmentioning
confidence: 99%